Overcoming body image problems including body dysmorphic disorder : a self-help guide using Cognitive Behavioral Techniques /: a self-help guide using Cognitive Behavioral Techniques. ([2012?]) - Veale, David; Willson, Rob; Clarke, Alex, 1953-
No abstract available